Primary orbital ganglioneuroblastoma: A case report - Ma Ruixin (De Gruyter, 2021)
Ganglioneuroblastoma (GNB) is a neoplasm that arises from the primitive cells of the sympathetic nervous system during childhood. The current case is very unique because of the initial primary tumor manifestation in the orbit and an adrenal tumor being observed later during follow-up.